2020
DOI: 10.1007/s10584-020-02925-w
|View full text |Cite
|
Sign up to set email alerts
|

Women’s empowerment and farmland allocations in Bangladesh: evidence of a possible pathway to crop diversification

Abstract: Climate change will likely affect several of the dimensions that determine people’s food security status in Bangladesh, from crop production to the availability and accessibility of food products. Crop diversification is a form of adaptation to climate change that reduces exposure to climate-related risks and has also been shown to increase diet diversity, reduce micronutrient deficiencies, and positively affect agro-ecological systems. Despite these benefits, the level of crop diversification in Bangladesh re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 63 publications
0
17
0
Order By: Relevance
“…Several studies have found positive associations between various empowerment measures and agricultural production indicators ( Anik and Rahman 2021 ; De Pinto et al, 2020 ; Diiro et al, 2018 ; Seymour 2017 ; Wouterse 2017 , 2019 ). For example, in Niger, empowerment scores are positively associated with agricultural output ( Wouterse 2017 , 2019 ).…”
Section: Additional Benefits To Closing the Empowerment Gapmentioning
confidence: 99%
“…Several studies have found positive associations between various empowerment measures and agricultural production indicators ( Anik and Rahman 2021 ; De Pinto et al, 2020 ; Diiro et al, 2018 ; Seymour 2017 ; Wouterse 2017 , 2019 ). For example, in Niger, empowerment scores are positively associated with agricultural output ( Wouterse 2017 , 2019 ).…”
Section: Additional Benefits To Closing the Empowerment Gapmentioning
confidence: 99%
“…Using the nationally-representative data from Bangladesh, Sraboni et al (2014) found a positive association between women's empowerment, production diversity, household calorie availability, and household dietary diversity. Other research using the same dataset found aspects of women's empowerment contributing to crop diversification from cereals to the production of fruits and vegetables (De Pinto et al 2020). While the original demand for WEAI was for a high-level number, the fact that it could be deconstructed into separate indicators and its data further disaggregated by other population characteristics was crucial for these types of analyses, as well as for providing guidance to projects on the areas where women (and men) had the greatest disempowerment, and how interventions could contribute to empowerment.…”
Section: What's Measured Mattersmentioning
confidence: 86%
“…Much of the existing literature on women's empowerment explores the ways in which women's empowerment contributes to other development outcomes, such as improvement in agricultural productivity ( Seymour, 2017 ), increase in production diversity ( De Pinto et al, 2020 ) or improved food security and nutrition ( Malapit and Quisumbing, 2015 ; Kassie et al, 2020 ). A growing body of literature examines the extent to which development interventions, including those that aim to increase women's access to and control over productive assets, support women's empowerment ( Cornwall, 2016 ; Johnson et al, 2016 ; Malapit et al, 2019 ; Anderson et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%